Financial Education for the Muncan Village Community Through Digital Media - Anak Agung Ketut JAYAWARSA; Komang Adi Kurniawan SAPUTRA; A.A. Ngurah Mayun NARINDRA (PT Keberlanjutan Strategis Indonesia, 2025)
This community service program aims to improve financial literacy in the Muncan Village community through the use of digital media. The majority of residents work in the agricultural and MSME sectors, with low financial literacy and limited access to formal financial information. The blended learning method used combines offline workshops and online mentoring via WhatsApp groups. Educational materials were delivered through animated videos, infographics, and posters tailored to the local context. The results showed an average increase in financial literacy of 42%. Eighty percent of participants understood the risks of saving at home, 75% understood the difference between saving in a bank and a piggy bank, and 70% could recognize the characteristics of illegal online loans. Furthermore, 25 participants began recording their finances, and 15 opened their first bank accounts. Digital media successfully transformed from a medium of entertainment into an educational tool, with the